The Value of Nature During Psychotherapy: A Qualitative Study of Client Experiences - Meuwese, Daphne; van der Voort, Nienke; Dijkstra, Karin; Krabbendam, Lydia; Maas, Jolanda (Frontiers in Psychology, 2021)
Nature is considered to have restorative qualities that can potentially improve psychotherapy success. However, little is known about how clients experience nature during psychotherapy. The research aim of this phenomenological qualitative study was to study how clients experience nature during individual outpatient psychotherapy that took place while walking in nature. More specifically we were interested in clients’ inner world experiences. All participants (N = 12) received treatment through licensed therapists for a DSM-5 classified disorder. Semi-structured interviews were conducted. To uncover true lived experiences during these interviews, participants were asked to close their eyes and envision themselves during a psychotherapy session in nature. The verbatim transcripts were coded by means of inductive thematic analysis and the results were member checked. Results showed that nature brings clients closer to their inner worlds. How nature brings this about is unfolded in a conceptual model of lived experience. We argue that psychotherapy can be enriched by considering nature as a supportive environment, because bringing clients closer to their inner worlds is of essential value in facilitating successful treatment interventions.